COMPARATIVE ANALYSIS OF FUNCTIONAL FOOD PRODUCERS PROFITABILITY IN SERBIA - A LEADER-FOLLOWER RELATION - Draganac, Dragana (Economics of Agriculture, 2016)
The functional food market in Serbia is relatively young and insuffciently explored both from the aspects of producers and consumers, the qualitative aspect and especially from the quantitative aspect. The aim of this paper is to illustrate the results of the comprehensive quantititative fnancial analysis of proftability which focuses on the example of two companies. The main criterion applied in the selection of companies for the analysis represents the fact that one company is recognizable as a producer of foods with nutritive and health claims and is a leader within that market segment, whereas the other analyzed company mostly produces traditional products and has entered the aforementioned market segment at a later stage. The key idea is to do a comparative analysis of the profitability of these two companies for a four-year period. The proftability ratio analysis and the Du Pont analysis system are used in the paper as well as the analysis of solvency and financial leverage effect. The vertical analysis of income statement is also done in order to reveal the relation between some cost categories and operating revenues. The research results lead to a conclusion that the company that mostly produces functional foods has higher proft margins and rates of return and is therefore in a more favourable position since it can beneft from positive effects of fnancial leverage to a higher extent. The proftability of the second relevant company is mostly based on the better asset turnover.